Back Cover: Tricycloquinazoline‐Based 2D Conductive Metal–Organic Frameworks as Promising Electrocatalysts for CO2 Reduction (Angew. Chem. Int. Ed. 26/2021). Issue 26 (5th May 2021) - Liu, Jingjuan; Yang, Dan; Zhou, Yi; Zhang, Guang; Xing, Guolong; Liu, Yunpeng; Ma, Yanhang; Terasaki, Osamu; Yang, Shubin; Chen, Long
Abstract : 2D conductive metal–organic frameworks show promising applications in electrocatalytic CO2 reduction to methanol. In their Research Article on page 14473, Yanhang Ma, Shubin Yang, Long Chen, and co‐workers report a new nitrogen‐rich tricycloquinazoline (TQ) copper(II) catecholate based MOF (Cu3 (HHTQ)2 ). This MOF exhibits high crystallinity, good electrical conductivity, and excellent electrocatalytic activity in CO2 RR with high selectivity for CH3 OH production.